FENOMENA JINGLE "OKE GAS": STUDI NETNOGRAFI KAMPANYE POLITIK DI TIKTOK - Tanuwijaya, Vincentius; M, Sherly Cristian (Perspektif Komunikasi: Jurnal Ilmu Komunikasi Politik dan Komunikasi Bisnis, 2024)
Social media, especially TikTok, plays an important role in political communication strategies in the digital era. TikTok is not only a medium for delivering messages but also supports direct interaction between presidential candidates and netizens through creative content. This research examines the phenomenon of the use of the "Oke Gas" jingle in the political campaign of the 02 presidential candidate pair in the 2024 Election. This research aims to determine the role of the type of content that uses the Oke Gas jingle on TikTok in attracting netizens' attention in the form of comments so that what sentiments occur can be seen with a netnography study. A total of six selected TikTok contents consisting of official campaign team uploads (owned content), influencers (earned content), netizen content (shared content), were analyzed to explore the sentiments that emerged, both positive, negative, and neutral. The results of the research showed that the use of jingles as a campaign element was effective in increasing interaction from netizens. The "shared content" category, such as creative videos from netizens that have a humorous nuance and casual theme, produced the highest positive sentiment. Meanwhile, "owned content" from campaign team uploads tends to generate negative sentiment due to different political preferences between netizens. Meanwhile, "earned content" from influencers can expand reach but attracts more attention to the influencer's personality than political messages. This research uses the hypodermic needle theory that shows the effectiveness of social media in influencing public opinion through visually and emotionally engaging content. The results of this research provide strategic input for political campaign teams to utilize TikTok as a tool by emphasizing the creativity of content that is relevant to netizens in order to be more effective in building public support.